CLEANING OF OIL CONTAMINATED WATERS USING BIOSORBENTS - Казанок, А. В.; Матвєєва, О. Л. (Science-based technologies, 2014)
Identified the main sources of oil contaminated wastewaters. Analyzed the features of wastewater pollution by oil products. Considered the basic methods of cleaning water from petroleum products. Identified the basic requirements that must be achieved in the purification of oil contaminated wastewaters. Identified the main flaws of existing methods of waste waters from petroleum. Analysed the features of wastewater treatment using biosorbents. Characterized the popular biosorbents in Ukraine «Ekolan-M», «Ekonadin», «Rodex-T». Explored the effectiveness of work biodestructors in conditions of variable physicochemical properties of oil contaminated water. Installed that optimal temperature for growth and development of microorganisms is a temperature of 28 ̊C. The most effective is microorganisms of oil sorbent «Ekolan-M». The chemical composition of the oil products affects the activity of microorganisms. The most favorable environment for the active growth has determined mixed type: the mixture of mineral and synthetic oil.